The Role of Green Financial Instruments, Monetary Policy, and Foreign Direct Investment in Promoting Sustainable Development in Developing ASEAN Countries - Mendrofa, Ezri Chen Eunike; Andaiyani, Sri (Organizations and Markets in Emerging Economies, 2025)
The global focus on sustainable development intensified with the introduction of the Sustainable Development Goals (SDGs) in 2015, with the primary aim of balancing economic growth, social well-being, and environmental responsibility. This research explores how green bonds, interest rate policies, and foreign direct investment (FDI) contribute to the progress of SDGs in four developing ASEAN nations: Indonesia, Malaysia, the Philippines, and Thailand. Using quarterly data from 2018 to 2023, the study applies the Panel Vector Error Correction Model (PVECM) to uncover the dynamics at work. The findings reveal that green bonds and foreign direct investment have a notable and positive effect on the SDG index in both the short and long term. On the other hand, the impact of policy interest rates is negative, though statistically insignificant, particularly when rates are high. These results provide valuable guidance for policymakers seeking to enhance the effectiveness of financial tools and investments in driving sustainable development. Furthermore, the study stresses the importance of well-rounded policy frameworks that integrate economic, social, and environmental objectives. Theoretically, this study contributes to the refinement of Ecological Modernization Theory by empirically demonstrating how green financing and FDI serve as pivotal instruments in advancing sustainable development within emerging ASEAN economies.